Preliminary study for customer’s online shopping satisfaction from security perspective - Imtiaz Ali, Najma; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Brohi, Imtiaz Ali; Shah, Asadullah (cience Publishing Corporation Inc, 2018)
The objective of this paper is to present the results of preliminary study that has been performed to measure the reliability of the ques-tionnaire for collecting the quantitative data for the proposed security model of online shopping satisfaction. This paper is endeavours of our previous paper, in which we have developed the research model. Quantitative methodology was adopted to conduct the study by collecting the data through survey questionnaire based on five point Likert scale. Statistical Package for the Social Sciences (SPSS) ver-sion 23.0 was used to analyse the data. Results shows that the Cronbach’s alpha value to ensure the reliability of the items is ≥ 0.7, It means all our variables are acceptable for the further studies and for the actual data collection. This paper conclude that the pilot study is necessary phase to conduct before going to collect the actual data in order to avoid any ambiguity in items. Although the sample data is small for the pilot study still, it shows the strength between the related items.